Students Critical Thinking Skills in a Classroom Debate - Handayani, Reli (LLT Journal: A Journal on Language and Language Teaching, 2016)
Mastering argumentative discourse both in written and oral is a must for students nowadays. However, a successful argumentative discourse requires high thinking order skill such as developing a stance, analyzing arguments, distinguishing facts and opinions, solving problems, comparing and contrasting material, and making inferences. Realizing the importance roles of critical thinking in constructing argumentative discourse, this study focuses on students performance in debate specifically argument, counter-argument, and rebuttals. They are chosen since they are always taken into consideration in assessing students debate performance.